Reviews of environmental contamination and toxicology. volume 213 - Whitacre, David M. (Reviews of environmental contamination and toxicology, continuation of residue reviews, 2011)
CONTENTS Foreword Preface Pesticidal Copper (I) Oxide: Environmental Fate and Aquatic Toxicity Lina Kiaune and Nan Singhasemanon Human Exposure, Biomarkers and Fate of Organotins in the Environment Hussein K. Okoro, Olalekan S. Fatoki, Folahan A. Adekola, Bhekumusa J. Ximba, Reinette G. Snyman, and Beatrice Opeolu Shellfish and Residual Chemical Contaminants: Hazards, Monitoring and Health Risk Assessment along French Coasts M. Guéguen, Marielle Guéguen, Jean-Claude Amiard, Nathalie Arnich, Pierre-Marie Badot, Didier Claisse, Thierry Guérin, and Jean-Paul Vernoux Lead Uptake, Toxicity and Detoxification in Plants Bertrand Pourrut, Muhammad Shahid, Camille Dumat, Peter Winterton and Eric Pinelli Before the Curtain Falls: Endocrine Active Pesticides - a German Contamination Legacy Ulrike Schulte-Oehlmann, Jörg Oehlmann, and Florian Keil Index.